Bioaccumulation and oxidative stress in Daphnia magna exposed to arsenite and arsenate. (21st October 2015) - Fan, Wenhong; Ren, Jinqian; Li, Xiaomin; Wei, Chaoyang; Xue, Feng; Zhang, Nan
Abstract Arsenic pollution and its toxicity to aquatic organisms have attracted worldwide attention. The bioavailability and toxicity of arsenic are highly related to its speciation. The present study investigated the differences in bioaccumulation and oxidative stress responses in an aquatic organism, Daphnia magna, induced by 2 inorganic arsenic species (As(III) and As(V)). The bioaccumulation of arsenic, Na+/K+‐adenosine triphosphatase (ATPase) activity, reactive oxygen species (ROS) content, total superoxide dismutase (SOD) activity, total antioxidative capability, and malondialdehyde content in D. magna were determined after exposure to 500 µg/L of arsenite and arsenate for 48 h. The results showed that the oxidative stress and antioxidative process in D. magna exposed to arsenite and arsenate could be divided into 3 phases, which were antioxidative response, oxidation inhibition, and antioxidative recovery. In addition, differences in bioaccumulation, Na+/K+‐ATPase activity, and total SOD activity were also found in D. magna exposed to As(III) and As(V). These differences might have been the result of the high affinity of As(III) with sulfhydryl groups in enzymes and the structural similarity of As(V) to phosphate. Therefore, arsenate could be taken up by organisms through phosphate transporters, could substitute for phosphate in biochemical reactions, and could lead to a change in the bioaccumulation of arsenic and activity of enzymes. These characteristics were the possible reasons for the different toxicity mechanisms in the oxidative stress process of arsenite and arsenate. Environ Toxicol Chem 2015;34:2629–2635. © 2015 SETAC